2006
DOI: 10.1177/0091270006286435
|View full text |Cite
|
Sign up to set email alerts
|

The Comparability of Etanercept Pharmacokinetics in Healthy Japanese and American Subjects

Abstract: Thirty Japanese (J) and 32 American (A) healthy subjects received single doses of etanercept by subcutaneous injection, in 3 separate trials. Serum samples were collected for 480 hours after dosing. Concentrations were determined using enzyme-linked immunosorbent assay methods. Pharmacokinetic parameters were calculated using both non-compartmental and compartmental methods. Etanercept was slowly absorbed, with mean+/-SD time to maximum serum concentration of 47+/-15 hours (J), and 51+/-20 hours (A). The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 14 publications
4
10
0
Order By: Relevance
“…The stability and extrapolation of the model developed in the present study need further improvement and evaluation in a larger group of subjects before the model can be fully validated. Interestingly, this analysis confirmed that the estimated population parameters in Chinese subjects were similar to those reported previously in other nations [20] . For example, CL/F was 0.110 L/h for Chinese males and 0.168 L/h for Chinese females, values similar to the CL/F values of 0.132±0.085 L/h (mean±SD) in American subjects.…”
Section: Wwwchinapharcom Fang Y Et Alsupporting
confidence: 90%
“…The stability and extrapolation of the model developed in the present study need further improvement and evaluation in a larger group of subjects before the model can be fully validated. Interestingly, this analysis confirmed that the estimated population parameters in Chinese subjects were similar to those reported previously in other nations [20] . For example, CL/F was 0.110 L/h for Chinese males and 0.168 L/h for Chinese females, values similar to the CL/F values of 0.132±0.085 L/h (mean±SD) in American subjects.…”
Section: Wwwchinapharcom Fang Y Et Alsupporting
confidence: 90%
“…Many pharmacokinetic studies of etanercept conducted in healthy subjects have shown that these biologic agents are well tolerated. [11,[18][19][20][21] In addition, a previous population-based pharmacokinetic study of etanercept indicated that the pharmacokinetics in rheumatoid arthritis and ankylosing spondylitis patients is similar to that in healthy volunteers. [22][23][24] Therefore, reconstituted lyophilized (25 mg mL) HD203 and Enbrel Ò can be expected to result in similar pharmacokinetics in the clinical setting.…”
Section: Discussionmentioning
confidence: 96%
“…In humans, etanercept is administered subcutaneously and requires ≈2 days to reach effective plasma levels 41 : this pharmacokinetic profile may be sufficient, given that the earliest onset of angiographic vasospasm and DCI is at least 3 days after SAH, with peak incidence at 7 to 8 days. The fact that SAH patients frequently undergo craniotomy procedures to repair ruptured aneurysms or to have a ventricular catheter placed (for monitoring intracranial pressure) makes the intrathecal route a viable option for local etanercept delivery.…”
Section: Discussionmentioning
confidence: 99%